In search for a robust design of environmental sensor networks. Issue 6 (19th March 2018) - Budi, Setia; Susanto, Ferry; de Souza, Paulo; Timms, Greg; Malhotra, Vishv; Turner, Paul
ABSTRACT: This paper presents an approach to the design of environmental sensor networks (ESN) which aims at providing a robust, fit-for-purpose network with minimum redundancy. A set of near optimum ESN designs is sought using an evolutionary algorithm, which incorporates redundancy and robustness as fitness functions. This work can assist the decision-making process when determining the number of sensor nodes and how the nodes are going to be deployed in the region of interest.